Efficacy and safety of repeated endoscopic radial incision and cutting procedure for benign esophageal stricture - Yuki Kano; Tomohiro Kadota; Atsushi Inaba; Hironori Sunakawa; Kenji Takashima; Keiichiro Nakajo; Tatsuro Murano; Kensuke Shinmura; Yusuke Yoda; Hiroaki Ikematsu; Tetsuo Akimoto; Tomonori Yano (Endoscopy International Open, 2023)
Background and study aims: Radial incision and cutting (RIC) is indicated for refractory benign esophageal strictures after curative treatment for esophageal cancer and has shown favorable short-term outcomes. However, re-stricture after RIC may occur in the long term, and RIC is performed repeatedly in such cases, but the efficacy and safety of repeated RIC are unclear. Therefore, we aimed to demonstrate the efficacy and safety of the repeated RIC for refractory benign esophageal strictures after surgical and non-surgical treatment. Patients and methods: Between April 2008 and September 2019, we enrolled patients who were treated with the first RIC for benign esophageal strictures. The RIC was indicated for the refractory stricture and repeatedly performed for re-refractory esophageal stricture after RIC. We retrospectively evaluated the 6-month refractory stricture-free rate, and adverse events (AEs) in the first RIC and repeated RICs. Results: Forty-six patients (39 men, 7 women; median age, 71 years, range 49–85) were included. RIC was performed once in 24 patients (non-repeated RIC group) and two or more times in 22 patients (repeated RIC group). In all patients, the 6-month refractory stricture-free rate after the first RIC were 42.3 %. In the repeated RIC group, the 6-month refractory stricture-free rate after the first and repeated RICs were 18.2 % vs 18.2 %, respectively. No AEs were noted. Conclusions: Repeated RIC could be effective in the short-term and safe even for patients with refractory benign esophageal stricture after the first RIC. However, it cannot be considered curative treatment for refractory stricture because of poor long-term results.